Aplikasi Pemesanan Jasa Nail Art dan Eyelash Extension Berbasis Website (Studi Kasus: Pretty Bloom) - Putri, Oktaviani Enjela; Priskila, Ressa (Universitas Palangka Raya, 2023)
Pretty Bloom is an individual business that is personally managed by the owner of Pretty Bloom, therefore the problem with the ordering system is currently done manually and recording customer schedules is also still done manually by recording order data on a smartphone. For this reason, Pretty Bloom must look for other alternatives in handling the ordering system and promotion system. Therefore a website was built that can manage, store, and place orders to market Nail Art and Eyelash Extension services. The methodology used in designing and building this website is the waterfall method with the stages of Requirement Definition, System and Software Design, Implementation and Unit Testing and finally, Integration and System Testing using Black Box Testing. From the test results using Black box Testing, all the features on the website can run according to their function. This website can be used by Pretty Bloom to manage Nail Art and Eyelash Extension service catalog data and ordering data. In addition, customers can use it to view price list information for Nail Art and Eyelash Extension services offered and can place orders through the website.